UJI BEDA KUALITAS PELAYANAN E-KTP DI KOTA SURAKARTA DAN KOTA SEMARANG - Susi Sulandari (JURNAL ILMU SOSIAL, 2014)
Public services as the focus of the discipline of Public Administration remains interesting to observe because of the services provided by government officials to the public is still considered unsatisfactory. One of the problems of service in Indonesia is about administrative services, services e – KTP (identity cards). Surakarta and Semarang, both have been doing identity card service. Based on thr results of the initial survey in two cities, there are still many obstacles faced in the creation of identity card service.In this study, researchers will try to describe the service quality of e – KTP in Surakarta and Semarang, and will see no different whether or not the service quality of e – KTP in both cities. Type research used in this study is a quantitative study. The population of all citizens  Surakarta  and Semarang aged over 17 years and over. Becauseof the breadth of both cities used the sampling area, the city of Surakarta elected Laweyan districts and sub- districts of Semarang Pedurungan elected. Then each district taken 100 respondentsby means accidental. Analysis using interpretation of data : use of frequency distribution table predetermined number of respondents in the sample, the average sought to determine the caregories of service quality based on the resulth of the research, supplemented by interviews with respondent and the data to test the hypothesis used different test calculation of services quality in the city of Surakarta and Semarang.The result of this study concluded that the quality of service both in the district e KTPPedurungan  Semarang and Surakarta in district Laweyan results showed good all categories, but it’s god when seen in different positions of the class interval, for the districtLaweyan  Surakarta both categories at the upper limit of the interval 3,11 where as in the district Pedurungan Semarang, good bit closer to the lower limit of interval is 2,89. Based on the calculation results obtained by different test t value is equal to 3,004 with a sig 0.04. because the siq < 0,05 then it can be concluded that Ho is rejected, meaning that the average quality of service in the district Laweyan e KTP Surakarta identuty card service quality in the district of Semarang Pedurungan is not same (different). When viewed from its average of the quality of services in the district Laweyan Surakarta better than the service quality of e KTP in district Pedurungan Semarang. However, the  different is very thin.